Pendidikan Politik Sebagai Usaha Partai Politik Menyemai Nilai-Nilai Pancasila dalam Kehidupan Keorganisasiannya - Wibowo, Arif Prasetyo; Yusuf, Nurbani (Universitas Negeri Malang, 2022)
This study aimed to describe the meaning of political education for political parties, the relationship between the party platform and Pancasila values, approaches, media, and methods used by political parties in political education, as well as obstacles and efforts of political parties in the implementation of political education. This study used a qualitative approach with a comparative study method. Data was collected using interviews, observation, and documentation studies. Political education carried out by political parties to their cadres was interpreted as an educational effort to improve the quality of human resources. The platform of political parties was a reflection of the values of Pancasila. The approaches, methods, and media parties used in political education were diverse. Obstacles and efforts of political parties in implementing political education, including funding and attendance of members, were resolved by making donations and completing the results of the minutes of each meeting.